Resilience, coping and Personal Factors of medical students at a Public University; Karachi, Pakistan - Anum Arshad Beg,; Sidra Kanwal,; Veena Kumari Karmani,; Zainab Mohammad Anjarwala, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess resilience levels of medical students, identify factors associated with it, and explore association between coping styles and resilience level among medical students. Method: The analytical, cross-sectional study was conducted at the Dow Medical College, Dow University of Health Sciences, Karachi, from February to June 2022, and comprised medical students regardless of gender and the academic year. Data was collected using self-administered socio-demographic form, Brief Resilience Scale and Brief Cope. Data was analysed using SPSS 28. Results: Out the 301 participants, 197(65.4%) were females and 104(34.6%) were males. The overall mean age was 20.7±1.849 years. Of the total, 132(43.9%) students had low resilience, with males having better resilience compared to females (p<0.001). Higher resilience was seen in year 1 students compared to those of clinical years (p=0.029). There was a significant positive correlation between high resilience and problem-focussed coping, while a significant negative correlation was found between resilience and avoidant and emotionally focussed strategies (p<0.05). There was a significant negative correlation between resilience levels and age (p<0.025). There was a significant difference in resilience scores with respect to the last grade point average, sleep hours, and hours spent studying (p<0.05). Conclusion: More than one-third medical students demonstrated low resilience, and the majority reported adopting emotion-focussed coping style. Key Words: Resilience, psychological, adaptation, psychological, demography, sleepension, genotype, somnolence, enzyme, immunosorbent assay, adenine, guanine